Multidimensional determinants of academic performance: Insights from undergraduate students in Moroccan universities - Zakaria Alj; Anas Bouayad (OmniaScience, 2024)
This research investigates the multifaceted determinants of academic performance in a large-scale study of 5,092 undergraduate students across diverse Moroccan universities. We delved into demographic, academic, psychological, societal, and lifestyle factors, providing a comprehensive analysis of potential influencers on academic success. These dimensions were identified as significant predictors of academic performance, as gauged by the students' Grade Point Average (GPA). The findings reveal the intricate and interconnected nature of these factors and their cumulative influence on a student's academic trajectory. Our study emphasizes the necessity for a holistic approach that integrates not only traditional academic strategies, but also psychological support, balanced lifestyle practices, and effective societal engagement. Our research underscores the rich interplay among these variables and offers a profound understanding of their collective impact on academic performance. The derived insights could be instrumental for educators, policymakers, and researchers striving to create strategies that amplify student success. While acknowledging the inherent limitations of the study, we believe the results serve as a pivotal guidepost in the ongoing quest to optimize student academic outcomes and overall well-being.